User experience and hemostatic efficacy: Comparative analysis of commercial agents in junctional and hepatic hemorrhage models - Kyle Patterson; Adelle M. Dagher; Meredith Lackie; Lauren M. Heyda; Zain Baig; John Mares; Justin Hutzler; J. T. Green; Woo Do; Jason S. Radowsky; Matthew Bradley; Brandon Propper; et al. (PLoS ONE, 2025)
Background/Objectives Hemorrhage is associated with most preventable combat-related deaths. Management of non-compressible truncal and junctional hemorrhage remains challenging, especially with prolonged evacuations. This study evaluated the efficacy of commercial topical hemostatic agents in uncontrolled hemorrhage models under coagulopathic conditions, examining differences based on applicator experience. Methods Sixty Yorkshire swine were randomized to 5 groups: Combat Gauze (CG), Celox Rapid (CR), ChitoSAM 100 (CS), EVARREST® Fibrin Sealant Patch (EP), and X-Stat 30 (XS). After 50% hemodilution, a 5 mm femoral arteriotomy or 6 cm liver laceration was created, and the agents were applied as per device instructions. Hemostatic agents were placed by experienced (≥5 previous applications) or non-experienced (<5 previous applications) users. Animals were then monitored for rebleeding for 60 minutes. Results In the junctional hemorrhage model, only ChitoSAM required more applications by novice applicators (2.3 vs. 1, p = 0.0104). No significant differences in rebleed rates among devices (CG 0%, CS 33%, CR 17%, EP 17%, XS 33%, p = 0.73) or by user experience were observed. No differences in perfusion were noted on angiography. In the hepatic laceration model, no significant differences in applications or rebleed rates for any agent (CG 0%, CS 50%, CR 17%, EP 17%, XS 0%, p = 0.21) or by user experience were found. Overall survival did not significantly vary by device. Conclusion All 5 hemostatic agents showed similar efficacy in controlling junctional and intra-abdominal hemorrhage, with no significant differences in hemostasis, rebleed rate, or survival by experience level. However, more ChitoSAM applications were needed for junctional hemorrhage control in the absence of experience. All tested dressings show promise for rapid hemorrhage control.